Customized Prosthetic Management for Post Orbital Exenteration Patient: A Case Report: Poster Presentation - Case Report - Resident - Uray Nabila Yuna; Raden Angga Kartiwa; Yudhistira Knoch (Majalah Oftalmologi Indonesia, 2023)
Introduction : Orbital exenterations are performed to treat malignancies, orbital injury or other chronic conditions unresponsive to conservative therapy. Exenteration can result in depression, difficulties in daily activities, and aesthetic problems. Orbital prosthetic is an alternative therapy for aesthetic rehabilitation and protection of the orbital cavity. Case Illustration : A 46-year-old woman came with a chief complain of a black mass on the left lower eyelid ten years ago. Patient was diagnosed with basal cell carcinoma and underwent extirpation of the mass with skin graft reconstruction. On histopathological examination, it was discovered that the incision base was not free of tumor. Patient came two years later with recurrent black mass invaded cornea and sclera, and then underwent exenteration of the left eye (Figure 1). Patient completed 40 cycles of radiotherapy and then used spectacle retained orbital prosthetic (Figure 2 & 3). Discussion : Orbital prosthetics are synthetic replacement after exenteration that can restores orbit, eyelid, eye and periorbita anatomy. Orbital prosthetic retention can be aided by attachment to spectacle, use of magnets, adhesives or osseointegrated implants. Spectacle retained orbital prosthetic is the easiest and the most affordable prosthetic to construct. Conclusion : Orbital defects rehabilitation improves physical and psychological well-being. Due to the complexity of prosthetic fabrication and production cost, retention of the orbital prosthetic with spectacles is the most suitable alternative treatment option in some cases, it is also the easiest prosthetic to construct and inexpensive.